2018
DOI: 10.1111/jocn.14283
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of giving and receiving care in traumatic brain injury: An integrative review

Abstract: Recommendations include the following: (i) formal inclusion of people with traumatic brain injury and families in care planning, (ii) routine risk screening for falls and challenging behaviour to ensure that controls are based on accurate assessment, (iii) formal orientation and training for novice nurses in the management of challenging behaviour, (iv) professional case management to guide access to services and funding and (v) personal skill development to optimise family functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…15 A recent review about experiences of giving and receiving care in TBI found that NPS, specifically verbal and physical aggression, hindered the provision of quality care and required the implementation of proactive nursing strategies to maintain safety for both patients with TBI and nurses. 16 Indeed, NPS may prompt prescription of psychotropic drugs. However, antipsychotics, prescribed for the treatment of psychosis, agitation, and aggression, may have adverse effects on cognition.…”
mentioning
confidence: 99%
“…15 A recent review about experiences of giving and receiving care in TBI found that NPS, specifically verbal and physical aggression, hindered the provision of quality care and required the implementation of proactive nursing strategies to maintain safety for both patients with TBI and nurses. 16 Indeed, NPS may prompt prescription of psychotropic drugs. However, antipsychotics, prescribed for the treatment of psychosis, agitation, and aggression, may have adverse effects on cognition.…”
mentioning
confidence: 99%
“…Few studies have explored what receiving care is like for sufferers of TBI (see Kivunja et al, 2018), and we could only locate a single study that considered women's experiences of receiving care post-TBI (see Alston et al, 2012). For Alston et al (2012), their participants also expressed having negative experiences of receiving care from their male-informal caregivers and similarly kept those sentiments from their partners.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ABI will benefit from this study. A recent review about experiences of giving and receiving care in TBI showed that NPS hindered the provision of quality care and required the implementation of proactive nursing strategies to maintain safety for both patients with TBI and nurses (Kivunja, River, & Gullick, ). Provision of quality care may be enhanced, e.g., by giving nursing home staff, who are responsible for the daily care of patients with ABI, the tools to improve handling NPS through educational programs.…”
Section: Discussionmentioning
confidence: 99%